Effectiveness The Positive Self Talk Method to Mental Trust Self Athlete Category fight Footprint Muhammadiyah University Prof. Dr. Hamka - Fauzan Hasbi; Asni Asni (Jurnal Paedagogy, 2023)
This study aims to analyze the effectiveness of positive self-talk on the athlete's mentality in the fighting category Tapak Suci UHAMKA. The method used for this study was method experiment one group pretest-posttest design with a quantitative approach. For taking a sample, this study used a purposive sampling technique. The research instrument was a pretest and posttest questionnaire that had been validated. Data analysis techniques using the Wilcoxon T test with the help of SPSS ver. 26 proved that Asymp. Sig.(2-tailed) = 0.012. Because the value of 0.012 <0.05, until Ho was rejected, there was a significant (real) effect. The conclusion from the results of this study is that positive self-talk was proven to be effective in improving the mentality of UHAMKA Tapak Suci fighting athletes. Research results implicat that if athletes and coaches know the method of Positive Self-Talk and are supported with the sufficient facility, then practice can be used as a variation from mental exercise to improve athlete confidence.